Will There be Condominiums in Data Space? - Viola, Bill (Farol, 2024)
A pioneer in the field of video art, Bill Viola is a seminal artist in understanding the issues related to this medium, both in its historical course and in its current times. Over the years, he sought to link the notions of media as a medium, highlighting that video channels are also channels for transmitting information equivalent to the energetic transductions of shamanic incorporations. In Will There Be Condominiums in Data Space?, initially published in 1982, Viola explores the past and future of issues related to memory, both mental and artificial, seeking to understand its trajectories and future. With his erudite thinking and anachronistic vision, Viola makes references to several authors, such as Ananda K. Coomaraswamy, Thomas Aquinas, Giordano Bruno, Giulio Camilo, Jacobos Publicius, Nikola Tesla, etc. He also shares personal experiences, such as his experience in Tibetan Buddhist monasteries and his interactions with the wise monks of Ladakh who, with a cyclical mentality, develop sophisticated colored sand mandalas. Furthermore, he reports an experience he had on his trip to Japan, in 1981, where he met the itako, blind shamans equipped with mediumistic knowledge, capable of accessing information and data before and beyond this time, communicating with the dead. Viola points out that, during this period, this experience made him review his conceptions about corporations and their devices, including cameras, televisions and magnetic strip video tapes which, until then, he considered to be far ahead in the development of communication technologies. In short, for the author, technological advances in collective storage in electronic data space — analog at the time and currently digital — have a profound relationship with ancestral knowledge, human memory, thought processes and conceptual structures in the brain.